Contribution to mango value chain development in Benin a producer perception survey - Melle, C. van; Arinloye, D.A.; Coulibaly, O.; Vayssières, Jean-François; Hell, K. (International Society for Horticultural Science, 2013)
Mango (Mangifera indica L., Anacardiaceae) is a popular fruit in Africabecause of its high nutritional and economic value. However, smallholders in Benin, aWest African country, are currently unable to take advantage of this potential becauseof various constraints along the value chain. A survey with 150 mango producers inthree agro-ecological zones revealed that producers estimate losses for graftedmangoes are 46% and for local mangoes 68%. They perceive phyto-sanitary problems(mainly fruit fly infestations) as well as poor access to markets as the main causes.Mango production in Benin is concentrated in the Northern Guinean Savannah (NGS)zone, and mostly done on small scale (80% ?3 ha) with no use of purchased inputs(extensive). Profitability is relatively low, varying from minus 60 to 80 USD/ha in NGSand slightly higher in the other zones. The distance of the orchard to the road (remoteness)shows a negative trend regarding the profit per kg mango produced, whichdemonstrates high transaction costs. In order to reduce mango losses and increaseprofitability, an integrated approach is needed, both addressing phyto-sanitaryproblems as well as poor market access. The development of alternative and innovativevalue chains can contribute to filling the resource gaps at producer level.